Community pharmacists’ attitudes, perceptions, and barriers toward adverse drug reaction reporting in Malaysia: a quantitative insight - Elkalmi, Ramadan Mohamed Mahmod; Hassali, Mohamed Azmi; Ibrahim, Mohamed Izham M; Jamshed, Shazia Qasim; Al-lela, Omer Qutaiba (Lippincott Williams & Wilkins, 2014)
Objectives: This study was designed to explore awareness and attitudes of community pharmacists toward the national ADR reporting system activities in the northern states of Malaysia. Methods: A cross-sectional survey using a validated self-administered questionnaire was used in this study. The questionnaire was delivered to all community pharmacists (N = 470) practicing in the four northern states of Malaysia (Perlis, Kedah, Pulau Pinang and Perak) during the study period. Results: A total of 470 survey forms were sent with one wave of re- minders. Only 116 pharmacists responded to the survey (response rate of 25.2%). The total number of usable responses was 104 (24.7%). The sur- vey findings revealed that nearly three-quarters of pharmacists (n = 75; 72.1%) were not aware of the pharmacovigilance activities run by the drug regulatory authority inMalaysia. Although more than half (n = 65, 61.5%) of the surveyed pharmacists emphasized the importance of ADR reporting, only 13 pharmacists (12.9%) claimed that they submitted ADR reports to the Malaysia Adverse Drug Reaction Advisory Committee (MADRAC) before this survey. Barriers which prevent community pharmacists from ADR reporting were identified. These included lack of knowledge on how to report (n = 36; 34.7%), the unavailability of reporting forms (n = 44; 42.6%), and ignorance of where the report should be sent to (n = 46; 44.6%). Conclusions: Despite the unfamiliarity and the common miscon- ceptions, the study results show that community pharmacists in the northern states of Malaysia have a very positive attitude toward the ADR reporting system in the country. However, the study findings highlight the urgent need for special education programs to establish continuous efforts to promote ADR reporting among community pharmacists. Further studies at the national level aimed at identifying and removing barriers that prevent community pharmacists from performing ADR reporting are required. Key Words: Pharmacovigilanc